Effect of negative shift of metalhydride cathode on the emission of H⁻ ions from penning discharge - Sereda, I.; Tseluyko, A.; Hrechko, Ya. (Вопросы атомной науки и техники, 2019)
On the basis of numerical calculations, the experimental results obtained by the authors in the study of the source of negative hydrogen ions of the Penning type with a metal hydride cathode are explained. It was shown that the yield of negative ions depends on the potential at the metal hydride cathode and is determined by the temperature of the plasma electrons. The dependence of this potential on the electron temperature is calculated numerically to ensure the maximum current of negative ions. На основі чисельних розрахунків пояснені експериментальні результати, які отримані авторами при дослідженні джерела негативних іонів водню типу Пеннінга з металогідридним катодом. Показано, що вихід негативних іонів залежить від потенціалу на металогідридному катоді і визначається температурою електронів плазми. Залежність цього потенціалу від температури електронів розраховується чисельно для забезпечення максимального струму негативних іонів. На основе численных расчетов объяснены экспериментальные результаты, полученные авторами при исследовании источника отрицательных ионов водорода типа Пеннинга с металлогидридным катодом. Показано, что выход отрицательных ионов зависит от потенциала на металлогидридном катоде и определяется температурой электронов плазмы. Зависимость этого потенциала от температуры электронов рассчитывается численно для обеспечения максимального тока отрицательных ионов.